Multicultural Education In The Concept Of The Philosophy Of Islamic Education - Fatmawati, Fatmawati (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This paper discusses multicultural education in the philosophy of Islamic education. The purpose of this research is to provide us with an understanding of multicultural education, which is a concept, idea, or philosophy as a set of beliefs and explanations that recognize and assess the importance of cultural and ethnic diversity in shaping lifestyles, social experiences, personal identities, and educational opportunities for individuals, groups, and countries. Such multicultural education must be implemented as soon as possible in educational practice. This is because education with a multicultural perspective is believed to be able to grow and develop students into individuals who are not only proud of themselves (the culture, language, and other specialties they have), but are also able to recognize, accept, and respect the different specialties that others have. They are ready to live in equality. Multicultural education has a conceptual relationship and its relevance to Islamic religious doctrine.